A 14 nucleotide deletion mutation in the coding region of the PpBBX24 gene is associated with the red skin of "Zaosu Red" pear (Pyrus pyrifolia White Pear Group): a deletion in the PpBBX24 gene is associated with the red skin of pear. (1st April 2020) - Ou, Chunqing; Zhang, Xiaoli; Wang, Fei; Zhang, Liyi; Zhang, Yanjie; Fang, Ming; Wang, Jiahong; Wang, Jixun; Jiang, Shuling; Zhang, Zhihong
Abstract: Red skin is an important quality trait for pear fruits and is determined by the concentration and composition of anthocyanins. The regulatory mechanism underlying anthocyanin accumulation is a popular topic in fruit research. Red mutants are ideal materials for studying the molecular mechanism of color diversity in pear. Although several red pear mutants have been cultivated and are in production, no exact locus containing the responsible genetic mutation has been identified. In this study, by combining the bulked segregant analysis with whole-genome sequencing, we identified a 14 nucleotide deletion mutation in the coding region of the PpBBX24 gene from the red pear mutant "Zaosu Red". We further verified that the deletion was present only in the red mutant of "Zaosu" and in its red offspring, which was different from that which occurred in other red pear fruits. This deletion results in a coding frame shift such that there is an early termination of the PpBBX24 gene and loss of key NLS and VP domains from PpBBX24. The lost domains may reduce or alter the normal function of PpBBX24. In addition, we found that the transcript levels of the PpMYB10 and PpHY5 genes in red samples were significantly higher than those in green samples, whereas the results for the normal-type PpBBX24 gene were the opposite. We ultimately revealed that the 14 nucleotide deletion mutation in the coding region of the PpBBX24 gene is associated with the red skin of the "Zaosu Red" pear. This finding of somatic mutational events will be helpful for breeding new red pear cultivars and for understanding the regulatory mechanisms involved in pear skin pigmentation.